Repeated Simpson's 1/3 and Backward Difference Schemes to Solve First Order Linear Fredholm Integro-Differential Equations - Aruchunan, Elayaraja; Sulaiman, J. (Universiti Teknologi MARA Sabah, 2010)
The main purpose of this paper is to demonstrate the applications of repeated Simpson’s 1/3 and backward difference schemes via Gauss-Seidel (GS) method for solving linear Fredholm integro-differential equations of the first order. In addition, the implementation and formulation of the proposed method are also presented. Numerical examples are publicized to illustrate the efficiency of the method.